Effects of Fish Oil Supplementation on Serum C-Reactive Protein Levels in Trained Individuals: A Systematic Review of Clinical Trials - Parivash Shekarchizadeh-esfahani; Leili Khaghani; Jahangir Karimian (Clinical nutrition research, 2025)
Exercise, especially when prolonged or highly intense, can temporarily increase inflammation in both trained and untrained individuals. C-reactive protein (CRP) is an established biomarker of inflammation. However, clinical trials assessing the impact of fish oil supplementation on CRP levels in trained individuals have yielded inconsistent and often contradictory results. The main objective of this study was to conduct a systematic review of clinical trials exploring the effects of fish oil supplementation on CRP levels among trained individuals. We performed structured searches on the PubMed, Scopus, and ISI Web of Science databases for articles published from the earliest available date until September 2023. Of the 385 articles found and screened, three clinical trials met our criteria for inclusion in this review. The results suggested that fish oil supplementation may help prevent spikes in CRP levels after exercise. However, only one of the three studies produced statistically significant findings. The differences in statistical significance among these studies could be due to variations in the study design, sample populations, dosages, and duration of supplementation. In summary, this systematic review provides evidence that fish oil supplementation can reduce circulating CRP levels in trained individuals. Additional studies with long-term follow-up and larger sample sizes are needed to investigate this effect further.